A content analysis of online news media reporting on the human papillomavirus vaccination programme in South Africa. Issue 2 (3rd July 2018) - Attipoe-Dorcoo, Sharon; Singh, Vedantha; Moodley, Jennifer
Abstract : Background: Cervical cancer is the leading cause of cancer-related deaths among females in South Africa. In 2014 South Africa launched a national human papillomavirus (HPV) vaccination programme for grade 4 girls attending public schools. Approximately 49% of South Africans have access to the Internet and the content and quality of vaccination information could play a role in vaccine awareness and decision-making. This study examined the content, accuracy and tone of online news articles reporting on the HPV vaccination programme in South Africa. Methods: South Africa national online news sites, online community/regional newspapers and two global aggregated online news search engines (Google News and Yahoo News) were searched for relevant articles using a comprehensive set of keywords. Articles published between January 1, 2014 and June 30, 2015 were assessed for commonly cited sources of information, tone of the headline and article, accuracy of information about vaccine characteristics, South Africa HPV vaccine programmatic details and information on HPV and cervical cancer. Results: A total of 56 articles were included in the analysis. The majority had a neutral headline tone ( n = 45) and positive overall article tone ( n = 38). Information on the dose of HPV vaccine administered during the South African vaccination campaign was accurately mentioned in 38 articles. Twenty articles accurately mentioned the vaccine was efficacious and 12 accurately mentioned herd immunity; however, details on side effects were mostly not mentioned in articles ( n = 8). Conclusions: The online media coverage of the South Africa HPV vaccination programme was generally positive with accurate but sometimes incomplete information.